2023
DOI: 10.1002/pan3.10450
|View full text |Cite
|
Sign up to set email alerts
|

Gardening for wildlife: A mixed‐methods exploration of the factors underlying engagement in wildlife‐friendly gardening

Abstract: Private domestic gardens are integral to cities and urban ecosystems. For example, they account for an estimated 27.4% of the urban area of Edinburgh, UK (Loram et al., 2007), 23% of Sheffield, UK (Gaston et al., 2005), and up to 36% of Dunedin, New Zealand (Mathieu et al., 2007). Because domestic gardens are generally divided and dispersed across multiple small private properties, governments have difficulty enforcing guidelines that might harness private gardens to policy goals regarding biodiversity loss (e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 97 publications
0
4
0
Order By: Relevance
“…The social acceptability of nature-based solutions can be supported by promoting awareness, effective communication, and resident engagement, such as by providing opportunities to participate in design and management (Lampinen 10.3389/frsc.2024.1327614 Frontiers in Sustainable Cities 13 frontiersin.org et al, 2022). Residents are not only users of their green spaces but also decision-makers of their yards (García-Antúnez et al, 2023). Previous research has shown that community-led ecological participation, such as community gardening, can increase biodiversity and wellbeing (Dennis and James, 2016).…”
Section: Implications For the Planning Of Urban Green Infrastructurementioning
confidence: 99%
See 1 more Smart Citation
“…The social acceptability of nature-based solutions can be supported by promoting awareness, effective communication, and resident engagement, such as by providing opportunities to participate in design and management (Lampinen 10.3389/frsc.2024.1327614 Frontiers in Sustainable Cities 13 frontiersin.org et al, 2022). Residents are not only users of their green spaces but also decision-makers of their yards (García-Antúnez et al, 2023). Previous research has shown that community-led ecological participation, such as community gardening, can increase biodiversity and wellbeing (Dennis and James, 2016).…”
Section: Implications For the Planning Of Urban Green Infrastructurementioning
confidence: 99%
“…Residential yards and gardens have also been shown to support considerable biodiversity (Goddard et al, 2010). Besides vascular plants (Thompson et al, 2004), evidence from beetles (Barratt et al, 2015), bumblebees (Gunnarsson and Federsel, 2014), birds (Paker et al, 2014), spiders (Otoshi et al, 2015), and mammals (Van Helden et al, 2020;Kristancic et al, 2022) point to the potential of urban yards and gardens as habitats for diverse species, with specific garden features such as vegetation characteristics (Paker et al, 2014;Van Helden et al, 2020;Kristancic et al, 2022), and management methods (Otoshi et al, 2015;García-Antúnez et al, 2023) shaping the patterns of diversity in these groups.…”
Section: Introductionmentioning
confidence: 99%
“…(Kimmig et al., 2020). Such efforts also improve the cooperation between groups of city residents with different interests (García‐Antúnez, 2023), and have promoted human‐wildlife harmony and guided management practices (Ghijselinck, 2023).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, recent studies highlighted a central role of garden owners’ attitudes and consciousness in either promoting or impeding wildlife-friendly gardening. Wildlife-friendly gardening is a multifaceted issue which is influenced by several factors, such as demographics, socio-demographic drivers, motivations for gardening (García-Antúnez et al, 2023; Philpott et al, 2020), and appreciation for nature (Clayton, 2007), as well as trust in environmental associations and access to biodiversity-related information (Coisnon et al, 2019) and various management practices (Goddard et al, 2013).…”
Section: Introductionmentioning
confidence: 99%